Quality of Life and Timing of Stoma Closure in Patients With Rectal Cancer Undergoing Low Anterior Resection With Diverting Stoma: A Multicenter Longitudinal Observational Study. Issue 4 (April 2016) - Herrle, Florian; Sandra-Petrescu, Flavius; Weiss, Christel; Post, Stefan; Runkel, Norbert; Kienle, Peter
Abstract : BACKGROUND: After low anterior resection for rectal cancer, creation of a diverting stoma is recommended. Data on the impact of a diverting stoma on quality of life are conflicting. Optimal timing of stoma closure in the setting of adjuvant chemotherapy is unclear. OBJECTIVE: The purpose of this study was to investigate the impact of a diverting stoma on quality of life in patients undergoing rectal cancer resection before and after stoma closure. Furthermore, the study was conducted to look at the timing of stoma reversal and the potential influence of factors such as adjuvant chemotherapy. DESIGN: This was a longitudinal, observational, multicenter study. SETTINGS: The study was conducted at 17 German colorectal centers. PATIENTS: Patients with rectal cancer who planned for elective curative surgery with creation of temporary diverting stoma were included. MAIN OUTCOME MEASURES: This longitudinal observational study assessed quality of life at 3 occasions using European Organisation for Research and Treatment of Cancer Quality of Life Questionnaire–Core Questionnaire/Colorectal Cancer Module before cancer resection, before stoma closure, and 6 months after stoma closure. Furthermore, the timing of stoma closure and continence were evaluated. RESULTS: A total of 120 patients (64% men; mean age, 63.2 ± 11.5 years) were analyzed. Longitudinal global quality of life was not influenced by the presence of a stoma. Several functional and GI symptom scales were markedly impaired after stoma creation. Physical, role functioning, and sexual interest recovered after stoma closure. Social functioning stayed impaired ( p < 0.0001). Median time to stoma closure was 5 months (range, 17 days to 18 months). A total of 3.4% of patients had very early stoma closure (within 30 days). Adjuvant chemotherapy delayed stoma closure (median, 5.6 vs 3.4 months without chemotherapy; p = 0.0001). LIMITATIONS: The study was limited by its missing quality-of-life data for sexual function. CONCLUSIONS: The presence of a stoma had a negative impact on social functioning and GI symptoms. However, this had no clinically relevant influence on global quality of life. Time to stoma closure was nearly doubled when patients underwent adjuvant chemotherapy. Abstract : Supplemental Digital Content is available in the text.